Effects of side walking training using rhythmic auditory stimulation on plantar foot pressure sagittal distribution, body sway and gait in stroke patients - Choi, Youngjun.; Oh, Hyunok.; Kim, Eunjung.; Choi, Kyunga (International Journal of Engineering and Technology, 2018)
The purpose of this study was to evaluate the effect of side walking training using rhythmic auditory stimulation(RAS) on plantar foot pressure sagittal distribution(PFPSD), body sway and gait ability of stroke patients. Thirty patients with stroke patients participated in this study. Participants were randomly assignment to the side walking using RAS group(SWRASG, n=10), the side walking group(SWG, n=10), and the control group(CG, n=10). PFPSD, body sway, dynamic gait index(DGI) and 10m walking test(10 MWT) were performed for evaluate of pre-and post-intervention in balance and gait ability of participants. As a result, the pre- to post-test measures revealed a significant effect in each group on the PFPSD, body sway, DGI and 10 MWT(p<0.05). The PFPSD, body sway, DGI and 10 MWT were higher in SWG(p<0.05) than in CG and it was the highest in SWRASG(p<0.05). The PFPSD, body sway balance and 10 MWT, DGI gait ability was higher in SWG and SWRASG than in CG(p<0.05). In conclusion, for stroke patients, side walking training using RAS is effective on the balance and gait ability.Â Â Â